2022
DOI: 10.1186/s12871-022-01874-4
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise alleviates ventilator-induced lung injury by inhibiting NLRP3 inflammasome activation

Abstract: Background Ventilator-induced lung injury (VILI) is caused by stretch stimulation and other factors related to mechanical ventilation (MV). NOD-like receptor protein 3 (NLRP3), an important innate immune component, is strongly associated with VILI. This study aimed to investigate the effect and mechanisms of aerobic exercise (EX) on VILI. Methods To test the effects of the PKC inhibitor bisindolylmaleimide I on PKC and NLRP3, male C57BL/6 mice (7 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…[ 39 ] In the process of RA, a variety of intersecting pathophysiological systems such as autoimmune inflammation and endocrine disorders jointly form an intricate NEI network. [ 40 ] Yang F et al found that the foot swelling of AA rats was reduced after manual acupuncture of ST36, the levels of TNF-α protein and other pro-inflammatory factors in the ankle joint were down-regulated, and the cellular immune network in the inflammatory site was enhanced (the cell network density was 230.00 on the first day of acupuncture; Cellular network densities at days 7 and 15 were 40.82 and 86.76, respectively), demonstrating that acupuncture can increase the strength of immune effects on target organs, and at the same time promote the differentiation of macrophages in the joint site to the M2 phenotype, and secrete cytokines that inhibit inflammation and promote tissue repair. [ 41 ] Ding Shasha et al observed 32 common signaling molecules of NEI network in the serum of 131 Wistar rats.…”
Section: Regulation Of “Neuron-endocrine-immune” Networkmentioning
confidence: 99%
“…[ 39 ] In the process of RA, a variety of intersecting pathophysiological systems such as autoimmune inflammation and endocrine disorders jointly form an intricate NEI network. [ 40 ] Yang F et al found that the foot swelling of AA rats was reduced after manual acupuncture of ST36, the levels of TNF-α protein and other pro-inflammatory factors in the ankle joint were down-regulated, and the cellular immune network in the inflammatory site was enhanced (the cell network density was 230.00 on the first day of acupuncture; Cellular network densities at days 7 and 15 were 40.82 and 86.76, respectively), demonstrating that acupuncture can increase the strength of immune effects on target organs, and at the same time promote the differentiation of macrophages in the joint site to the M2 phenotype, and secrete cytokines that inhibit inflammation and promote tissue repair. [ 41 ] Ding Shasha et al observed 32 common signaling molecules of NEI network in the serum of 131 Wistar rats.…”
Section: Regulation Of “Neuron-endocrine-immune” Networkmentioning
confidence: 99%